The sin of certainty eaudiobook Why god desires our trust more than our "correct" beliefs. - Enns, Peter (Tantor Media, 2016)
With compelling and often humorous stories from his own life, Bible scholar Peter Enns offers a fresh look at how Christian life truly works, answering questions that cannot be addressed by the idealized traditional doctrine of "once for all delivered to the saints." Enns offers a model of vibrant faith that views skepticism not as a loss of belief, but as an opportunity to deepen religious conviction with courage and confidence. This is not just an intellectual conviction, he contends, but a more profound kind of knowing that only true faith can provide. Combining Enns's reflections of his own spiritual journey with an examination of Scripture, The Sin of Certainty models an acceptance of mystery and paradox that all believers can follow and why God prefers this path because it is only this way by which we can become mature disciples who truly trust God. It gives Christians who have known only the demand for certainty permission to view faith on their own flawed, uncertain, yet heartfelt, terms.